Financial Analysis of Finance Companies in Pokhara: A Comparative Study of Pokhara Finance Ltd. and Annapurna Finance Company Ltd. - Upadhyay, Krishna Prasad (Journal of Nepalese Business Studies, 2006)
Every business entity should be able to enhance their competitive strength through achieving the financial goals. Financial statement analysis should be adopted to appraise the financial performance of the concerned companies. Information and results obtained from financial analysis are important to all stakeholders. Interest of the different stakeholders is conflicting. Out of different stakeholders, managements of the companies worry about their financial performance. So, in this paper, an attempt to analyze the financial performance of Pokhara Finance Company and Annapurna Finance Company has been made. Journal of Nepalese Business Studies Vol.1(1) 2004 pp.101-106